Abnormal Static and Dynamic Functional Network Connectivity in Patients With Presbycusis - Xing, Chunhua; Chen, Yu-Chen; Shang, Song’an; Xu, Jin-Jing; Chen, Huiyou; Yin, Xindao; Wu, Yuanqing; Zheng, Jin-Xia (Frontiers in Aging Neuroscience, 2022)
Purpose: This study aims to investigate abnormal static and dynamic functional network connectivity (FNC) and its association with cognitive function in patients with presbycusis. Methods: Sixty patients with presbycusis and sixty age-, sex-, and educational matched healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rs-fMRI) and cognitive assessments. Group independent component analysis (ICA) was carried out on the rs-fMRI data, and eight resting state networks (RSNs) were identified. Static and dynamic FNCs were then constructed to evaluate differences in RSN connectivity between presbycusis patients and HCs. Furthermore, the correlations between these differences and cognitive scores were analyzed. Results: Presbycusis patients had differences in static FNC (sFNC) compared with HCs, mainly reflected in decreased sFNC in the default mode network (DMN)-left frontoparietal network (LFPN) and attention network (AN)-cerebellum network (CN) pairs, but they had increased sFNC in the auditory network (AUN) between DMN domains. The decreased sFNC in the DMN-LFPN pair was negatively correlated with their TMT-B score (r = -0.441, p = 0.002). Presbycusis patients exhibited aberrant dynamic FNCs in State 2, and decreased dFNCs between the CN and AN and the visual network (VN). Moreover, the presbycusis group had a shorter mean dwell time (MDT) and fraction time (FT) in State 3 (p = 0.0027; p = 0.0031, respectively). Conclusion: This study highlighted differences in static and dynamic functional connectivity in presbycusis patients and suggested that FNC may serve as an important biomarker of cognitive performance, since abnormal alterations can better track cognitive impairment in presbycusis.